1977
DOI: 10.1128/aac.11.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Anaerobic Bacteria to Metronidazole, Ornidazole, and Tinidazole and Routine Susceptibility Testing by Standardized Methods

Abstract: A total of 114 strains ofanaerobic bacteria were examined for their susceptibility to metronidazole, ornidazole, and tinidazole by measuring the minimum inhibitory concentration (MIC) and minimum bactericidal concentration in different media. All strains, with the exception of the isolates ofPropionibacterium acnes, were inhibited by 3.1 ug each and killed by 6.3 ,ug each of all three nitroimidazole compounds per ml. No significant differences in MIC values were found among metronidazole, ornidazole, and tinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 36 publications
5
21
0
2
Order By: Relevance
“…Metronidazole has significant in vitro activity against virtually all obligate anaerobes at readily achievable blood levels (13,20). Previously the microaerophilic and anaerobic streptococci, Actinomyces and Propionibacterium have been reported to be resistant (13); our data are in agreement with those observations.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Metronidazole has significant in vitro activity against virtually all obligate anaerobes at readily achievable blood levels (13,20). Previously the microaerophilic and anaerobic streptococci, Actinomyces and Propionibacterium have been reported to be resistant (13); our data are in agreement with those observations.…”
Section: Discussionsupporting
confidence: 83%
“…Wurst (20) reported the susceptibilities of 114 strains of anaerobes to ornidazole and metronidazole. All of his strains, except seven isolates of P. acnes, were inhibited by c3.1 jig of both agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bile, tinidazole levels initially rose more slowly but from about 12 h after the dose, the bile levels were similar to those in the serum sample taken at the same time. Reynolds et al (1975) and Wust (1977) found minimal inhibitory concentrations of tinidazole for common anaerobic pathogenic bacteria not greater than 3.1 ug/ml. This suggests that in our cases antibacterial levels were reached in the blood within 2 h of a 2 g oral dose and persisted for at least 24 h.…”
Section: Comparison Ofthe Two Methodsmentioning
confidence: 99%
“…The antimicrobial mechanism of ornidazole involves the formation of a hydroxylamine intermediate in the microbe, which damages microbial DNA, disrupts transcription, and ultimately causes cell death (Edwards, 1979;Muller, 1983;Kedderis et al, 1989). Ornidazole, which is similar in activity to metronidazole, shows a longer half-life (14.4 hours) than metronidazole (8.4 hours) and has reduced dosage frequency and duration of therapy in many relevant clinical infections (Schwartz and Jeunet, 1976;Wust, 1977;Goldstein et al, 1978). Ornidazole is usually administered orally, intravenously, intravaginally, or rectally as racemates in clinical practice.…”
Section: Introductionmentioning
confidence: 99%